Optimizing Pb-Ag Recovery Rate in the Flotation Process of Polymetallic Ores from the Northern Andean Region of Peru through Mineralogical Characterization - Valverde Díaz, José David (2025)
A mineralogical characterization study to optimize lead-silver (Pb-Ag) recovery rate by flotation was conducted at three adits named Esmeralda, Orión, and Hércules. The variables investigated included the dosage of the reagent blend (AP-3418/AR-404), AR-242, and pH. At the Esmeralda adit, a recovery of 81.99% lead at a concentrate grade of 58.66% and 83.79% silver at a head grade of 310.64 oz/t was achieved using a dosage of 18 g/t reagent blend (AP-3418/AR-404), 5 g/t AR-242, and an optimum pH value of 11.5. At the Orión adit, a recovery of 81.71% lead at a concentrate grade of 61.6%, and 81.24% silver at a head grade of 85.39 oz/t were achieved using a dosage of 30 g/t reagent blend (AP-3418/AR-404), 5 g/t AR-242, and an optimum pH value of 10.5. Finally, at the Hércules adit, a recovery of 82.4% lead at a concentrate grade of 54.12%, and 80.88% silver at a head grade of 62.63 oz/t grade were achieved using a dosage of 30 g/t reagent blend (AP-3418/AR-404), 15 g/t AR-242, and a pH value of 11.5.